Drug stabilization in the gastrointestinal tract and potential applications in the colonic delivery of oral zein-based formulations - Tran, Phuong H.L.; Duan, Wei; Lee, Beom Jin; Tran, Thao T.D. (International Journal of Pharmaceutics, 2019)
In recent years, various oral dosage forms using biomaterials have been developed to deliver drugs to the colon for therapy due to the advantages of local treatment and its ideal location for drug delivery. To achieve site-specific delivery, the complete drug should be released in the colon, while the drug must be protected or their delivery minimized in the stomach and small intestine. The use of natural or synthetic polymers has been reported for these purposes. The roles of zein in drug delivery have been identified with various types of formulations for improving bioavailability, controlled drug release and targeted delivery. Although zein has been demonstrated as a potential material for pharmaceutical applications, a review of zein in the gastrointestinal tract for stabilizing drug- and colon-specific delivery is still missing. In the present review, we aim to provide typical strategies for using zein in formulations to minimize drug release/ensure drug protection in the upper part of the gastrointestinal tract. Furthermore, effective fabrications or modifications for drug release in the colon will be highlighted. This primary resource of related methods of using zein in the gastrointestinal tract will advance technologies for using it as a natural polymer for drug delivery.
Keywords: Administration, Oral; Animals; Gastrointestinal Tract; Zein; Colon-specific delivery; Controlled drug release; Drug stabilization; Oral delivery; Zein